The Crisis of Turkestan Autonomy from the Perspective of Historians - Mutallibjonov Boburmirzo (International Journal of Formal Education, 2025)
This article analyzes the crisis of the Turkestan autonomy from the point of view of historians. The introduction provides brief information about the formation and political significance of the autonomy, as well as the relevance of the topic and the purpose of the scientific study. The methodology section describes the analysis of historical sources and the use of comparative historical methods, creating a basis for scientific research. The main part examines in detail the external and internal problems of the Turkestan autonomy, the weakness of national unity, disagreements between political groups, and the lack of a military strategy. According to historians, the political and military pressure of the Soviet authorities was a serious obstacle to maintaining the autonomy's independence, and internal conflicts were singled out as the main factors that undermined stability. The results show that the Turkestan autonomy's short-term crisis is explained not only by foreign political influence, but also by the low level of national awakening and the weakness of the political strategy. This study serves to deepen the understanding of the history of national independence movements in Central Asia and plays an important role in political historiography.